Secondary education students' views and use of GenAI for school work - quantitative survey data with 1266 respondents - Wickberg Hugerth, Mattias (Stockholm University, 2025)
This item contains a csv-file data collected through a survey distributed to upper secondary schools in Sweden during spring 2024. 1266 respondents from 9 different schools answered questions about their knowledge about, attitudes towards and use of generative AI for school work, in addition to background questions and questions about support from schools. Most questions are answered on a five-point likert scale. The file also contains columns with factor scores obtained through a confirmatory factor analysis, details of which can be found in the associated publication.

In addition to the csv-file, an excel file with variable names, survey questions and scales (in Swedish) is provided, as well as a pdf-version of the questionnaire used (in Swedish). Respondents answered in a digital interface with the same content in a different interface.
Keywords: Educational technology and computing; Educational Sciences; Utbildningsvetenskap